A Person-Centered Analysis of Motivation for Physical Activity and Perceived Neighborhood Environment in Residents of Assisted Living Facilities - Park, S.; Ntoumanis, Nikos; Fenton, S.; Stenling, A.; Veldhuijzen van Zanten, J.; Thogersen-Ntoumani, Cecilie (2018)
This study sought to identify profiles of individual, social, and perceived neighborhood environmental correlates of physical activity (PA) and to explore differences between the identified profiles in PA. Residents of assisted living facilities (N = 87, M age = 77.57 years) were recruited for the cross-sectional study. Participants reported their perceived support from important others for PA, basic psychological need satisfaction and motivation for PA, and perceived neighborhood environment around the assisted living facilities. Engagement in light PA and moderate-to-vigorous PA was measured by accelerometers over 1 week. We identified three profiles using latent profile analysis: ‘low self-determined and minimally supported', ‘moderately self-determined and supported', and ‘highly self-determined and supported'. Results showed participants in the highly self-determined and supported profile engaged in higher levels of light PA and moderate-to-vigorous PA than participants from other profiles. Findings showed perceptions of the neighborhood environment should be taken into account with motivation regarding PA.